Soluble fms-like tyrosine kinase-1 to placental growth factor ratio: ruling out pre-eclampsia for up to 4 weeks and value of retesting - Zeisler, H; Llurba, E; Chantraine, F; Vatish, M; Staff, A; Sennström, M; Olovsson, M; Brennecke, S; Stepan, H; Allegranza, D; Schoedl, M; Grill, S; et al. (Wiley, 2019)
Objectives: The soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to placental growth factor (PlGF) ratio is generally elevated some time before and at the clinical onset of pre‐eclampsia. The PROGNOSIS study validated a sFlt‐1/PlGF ratio cut‐off of ≤ 38 to rule out the onset of pre‐eclampsia within 1 week of testing in women with suspected disease. The aim of this study was to assess the predictive value of the sFlt‐1/PlGF ratio to rule out the onset of pre‐eclampsia for up to 4 weeks, and to assess the value of repeat measurements. Methods: This was an exploratory post‐hoc analysis of data from the PROGNOSIS study performed in pregnant women aged ≥ 18 years with suspected pre‐eclampsia, who were at 24 + 0 to 36 + 6 weeks' gestation at their first clinic visit. Serum samples were collected at the first visit and weekly thereafter. sFlt‐1 and PlGF levels were measured using Elecsys® sFlt‐1 and PlGF immunoassays. Whether the sFlt‐1/PlGF ratio cut‐off of ≤ 38 used to rule out the onset of pre‐eclampsia within 1 week could predict the absence of pre‐eclampsia 2, 3, and 4 weeks post‐baseline was assessed. The value of repeat sFlt‐1/PlGF testing was assessed by examining the difference in sFlt‐1/PlGF ratio 2 and 3 weeks after the first measurement in women with, and those without, pre‐eclampsia or adverse fetal outcome. Results: On analysis of 550 women, sFlt‐1/PlGF ratio ≤ 38 ruled out the onset of pre‐eclampsia 2 and 3 weeks post‐baseline with high negative predictive values (NPV) of 97.9% and 95.7%, respectively. The onset of pre‐eclampsia within 4 weeks was ruled out with a high NPV (94.3%) and high sensitivity and specificity (66.2% and 83.1%, respectively). Compared with women who did not develop pre‐eclampsia, those who developed pre‐eclampsia had significantly larger median increases in sFlt‐1/PlGF ratio at 2 weeks (∆, 31.22 vs 1.45; P < 0.001) and at 3 weeks (∆, 48.97 vs 2.39; P < 0.001) after their initial visit. Women who developed pre‐eclampsia and/or adverse fetal outcome compared with those who did not had a significantly greater median increase in sFlt‐1/PlGF ratio over the same period (∆, 21.22 vs 1.40; P < 0.001 at 2 weeks; ∆, 34.95 vs 2.30; P < 0.001 at 3 weeks). Conclusion: The Elecsys® immunoassay sFlt‐1/PlGF ratio can help to rule out the onset of pre‐eclampsia for 4 weeks in women with suspected pre‐eclampsia. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.